2018
DOI: 10.1371/journal.pgen.1007825
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Drosophila species learn dialects through communal living

Abstract: There is an instance of data duplication in the Supporting Information item S1 File. The underlying numerical data supplied for Figs 2A and 2B are identical. Please view the corrected version of S1 File below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
(1 reference statement)
0
6
0
Order By: Relevance
“…In one study, researchers found that the willingness of individuals to share or withhold information from competitors is influenced by the composition of the social environment, which they coined "audience effects" (53). In Drosophila, audience effects may explain why flies signal fertile oviposition sites (16,54) and the presence of predators to naïve flies (18). In the wild, flies may readily organize and transmit valuable information about their environment if the benefits of cooperation exceed the cost of competition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, researchers found that the willingness of individuals to share or withhold information from competitors is influenced by the composition of the social environment, which they coined "audience effects" (53). In Drosophila, audience effects may explain why flies signal fertile oviposition sites (16,54) and the presence of predators to naïve flies (18). In the wild, flies may readily organize and transmit valuable information about their environment if the benefits of cooperation exceed the cost of competition.…”
Section: Discussionmentioning
confidence: 99%
“…Flies display collective feeding strategies and collective escape responses, and they communicate the presence of predators and parasites (17). They engage in social learning (18)(19)(20) and display aggression (21). When a diseased individual is present, group dynamics are altered (22).…”
mentioning
confidence: 99%
“…In one study, researchers found that the willingness of individuals to share or withhold information from competitors is influenced by the composition of the social environment, which they coined “audience effects” [46]. In Drosophila , audience effects may explain why flies signal fertile oviposition sites [6, 7] and the presence of predators to naïve flies [10, 11]. In the wild, flies may readily organize and transmit valuable information about their environment if the benefits of cooperation exceed the cost of competition.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that social communication across drosophilids is conserved, given that drosophilids are known to encounter and interact with other species [47]. Recent work uncovered that drosophilids can socially signal the presence of predators to an unrelated heterospecific species [11], suggesting that flies communicate in “dialects” with each other. When considering complex social organization behaviours, the ecological pressures of a species’ environment play a large role in shaping these phenotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation